Clinical case of lysosomic acid lipase deficiency – cholesterol ethers accumulation diseases - E. V. Savelieva; A. P. Pakhomov; A. A. Vyalkova; V. V. Tyrsin; I. V. Zorin; E. V. Azarova; A. I. Meshcheryakova (Лечащий Врач)
Lysosomal acid lipase deficiency is a rare hereditary fermentopathy. Cholesterol ester accumulation disease – one of the two forms of lysosomal acid lipase deficiency – is a hereditary autosomal recessive lysosomal accumulation disease caused by mutations in the gene responsible for lysosomal acid lipase, as a result of which the activity of this enzyme is significantly reduced. As a result of a decrease or complete absence of lysosomal acid lipase activity, cholesterol esters and triglycerides are not hydrolyzed and accumulate in the lysosomes of the body's cells, including macrophages, endothelial cells, hepatocytes. The main clinical manifestation of lysosomal acid lipase deficiency is progressive liver damage with the development of hepatomegaly, increased levels of transaminases and/or microvesicular or mixed steatosis, due to the accumulation of cholesterol esters and triglycerides. Lysosomal acid lipase deficiency is a life-threatening genetic disease associated with an increased risk of premature death. The frequency of lysosomal acid lipase deficiency is 1:40 000-1:300 000. Studies on the frequency of occurrence of lysosomal acid lipase deficiency in Russia have not been conducted; the expected frequency is 1:100,000. This article presents a clinical case of lysosomal acid lipase deficiency – a disease of accumulation of cholesterol esters, hereditary deficiency of glucose-6-phosphate dehydrogenase in a 10-year-old child. The data of clinical and paraclinical examination of the patient, medical documentation, scientific literature were analyzed. Modern approaches to the management of pediatric patients with this pathology are presented. The peculiarity of this clinical case is a combination of three fermentopathies (deficiency of glucose-6-phosphate dehydrogenase activity of erythrocytes, deficiency of lysosomal acid lipase, decrease in functional activity of UDP – glucasyltransferase protein). The difficulty of differential diagnosis at the onset of the disease was the predominance of nonspecific symptoms of the disease: fever to febrile digits, vomiting, diarrhea – against the background of drug therapy, jaundice of the skin and sclera, dark urine color, hepatosplenomegaly. The prognosis for the disease of accumulation of cholesterol esters depends on the age of the manifestation of the disease and the severity of clinical manifestations. Timely diagnosis and appointment of pathogenetic therapy in the early stages of the disease determines a favorable prognosis and improves the quality of life of children with the disease of accumulation of cholesterol esters, preventing the development of cirrhosis of the liver.